1998
DOI: 10.3109/10641969809053208
|View full text |Cite
|
Sign up to set email alerts
|

Ouabain Produces Diverse Excitatory Effects on Afferent Baroreceptor Nerve Activity in SHR and WKY Animals

Abstract: The effect of acute ouabain treatment was evaluated on afferent baroreceptor nerve activity in spontaneously hypertensive rats (SHR) compared with Wistar Kyoto rats (WKY). Under urethane anesthesia (1.2 mg/Kg) the discharge of the recurrent laryngeal nerve was utilized as index of arterial baroreceptor activity (BNA) in rats with the ipslateral vagus cut at a proximal level. The ouabain (30 micrograms, i.v.) treatment produced an excitatory effect on BNA without changes in basal arterial pressure in both group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
12
1

Year Published

1999
1999
2007
2007

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 13 publications
2
12
1
Order By: Relevance
“…In rats with chronic SAD, the same treatment for only 5 days increased BP to the same extent as in intact rats treated with ouabain for 12 days. Consistent with a previous study, 13 the present study shows that, in Wistar rats, ouabain administered peripherally sensitizes arterial baroreflex function. Thus, in rats treated long term with ouabain, it appears that, sensitization of the arterial baroreflex temporarily inhibits central sympathoexcitatory and pressor effects of ouabain and that the central effects of ouabain at the present dose prevail after a few days of delay.…”
Section: Baroreflex Sensitization and Exogenous Ouabain-induced Hypersupporting
confidence: 81%
See 1 more Smart Citation
“…In rats with chronic SAD, the same treatment for only 5 days increased BP to the same extent as in intact rats treated with ouabain for 12 days. Consistent with a previous study, 13 the present study shows that, in Wistar rats, ouabain administered peripherally sensitizes arterial baroreflex function. Thus, in rats treated long term with ouabain, it appears that, sensitization of the arterial baroreflex temporarily inhibits central sympathoexcitatory and pressor effects of ouabain and that the central effects of ouabain at the present dose prevail after a few days of delay.…”
Section: Baroreflex Sensitization and Exogenous Ouabain-induced Hypersupporting
confidence: 81%
“…10,12 Peripherally administered ouabain can sensitize arterial baroreceptors. 13 This sensitization may be responsible for temporarily offsetting central pressor effects of ouabain, thereby leading to the delay of ouabain-induced hypertension.Digoxin is structurally similar to ouabain but has been reported to prevent ouabain-induced hypertension in normo- …”
mentioning
confidence: 99%
“…In contrast to our previous observations in spontaneously hypertensive rats, 7 in the present study, we observed that ouabain injection did not increase BNA in DOCA-salt and 2K1C hypertensive rats. A reasonable explanation for the enhanced response of spontaneously hypertensive rats to ouabain could be an active mechanism of production of ouabain-like substances in this strain.…”
Section: Discussioncontrasting
confidence: 56%
“…4,5 Ouabain, which is known as an inhibitor of Na ϩ -K ϩ -ATPase pump activity, reportedly has an excitatory effect on BNA. 6,7 Recently, we reported that the excitatory effect of ouabain on BNA is increased in spontaneously hypertensive rats. 7 The purpose of the present study was to determine whether ouabain has an excitatory effect on BNA in deoxycorticosterone acetate (DOCA) salt and 2-kidney, 1 clip (2K1C) hypertensive rats.…”
mentioning
confidence: 99%
See 1 more Smart Citation